Medical Waste during COVID-19 Pandemic: Its Types, Abundance, Impacts and Implications - Tang, Kuok Ho Daniel (Tecno Scientifica Publishing, 2022)
COVID-19 has resulted in an abrupt and significant increase in medical waste, albeit with improving air and water quality in certain regions. This paper aims to review the types, abundance, and impacts of COVID-19-related medical waste through examining the contents of 54 peer-reviewed scholarly papers. COVID-19-related medical waste compositions vary over time, with COVID-19 screening, diagnostic, and treatment wastes, as well as used personal protective equipment (PPE), constituting the majority of medical waste at the start, followed by vaccination waste during the peak of vaccination. COVID-19-related medical waste is expected to decrease and steady as more and more countries relax restrictions in an attempt to live with COVID-19. Geographically, the amount of COVID-19-related medical waste depends on population size, with highly-populated countries and cities such as China, Manila, Jakarta, and Bangkok seeing or expected to see a hike in the waste of between 210 tonnes/day and 280 tonnes/day during COVID-19. Packaging of the medical and PPE items forming the medical waste stream also contributes to a substantial amount of waste. As plastics are a major component of medical waste, the increase in COVID-19-related medical waste and its mismanagement have worsened environmental pollution caused by plastics. The surge of medical waste during COVID-19 strained the existing medical waste disposal systems, and incineration of the waste contributed to air pollution, which was often localized. Mismanagement of the waste could also raise public health concerns and cause visual repercussions.